Association between chronic pancreatitis and pancreatic cancer: A 10‐year retrospective study of endoscopically treated and surgical patients. Issue 5 (3rd April 2020) - Korpela, Taija; Udd, Marianne; Mustonen, Harri; Ristimäki, Ari; Haglund, Caj; Seppänen, Hanna; Kylänpää, Leena
Abstract : Pancreatic cancer (PC) has a poor prognosis. Chronic pancreatitis (CP) associates with high morbidity and mortality, and serves as a risk factor for PC. Our study aimed to assess the association between endoscopically treated CP patients and PC, and to establish the rate of CP among patients undergoing surgery for pancreatic ductal adenocarcinoma (PDAC). We retrospectively analyzed 458 CP patients undergoing endoscopic treatment (ET) between 2000 and 2010 and 349 PDAC patients undergoing pancreatic resection between 2000 and 2014 at the Helsinki University Hospital. The likelihood of diagnosing PC was highest within 2 years of a CP diagnosis: 21 of 30 PC diagnoses occurred during this time. After 2 years follow‐up: 9 of 30 PC diagnoses occurred 2–12 years from CP diagnosis. Two patients were diagnosed with CP before PDAC. Multivariate analysis showed two prognostic factors indicative of PC development: biliary stricture (HR 9.21; 95% CI 3.76–22.08) and a higher age (per 5‐year increases) at CP onset (HR 1.55; 95% CI 1.30–1.85). Among 458 CP patients, the median overall survival without PC was 14.7 years (95% CI 12.0–17.3), falling to 1.6 years (95% CI 1.2–2.0) with PC. The high incidence of PC among CP patients at the beginning of follow‐up likely reflected an initially missed PC diagnoses. In long‐term follow‐up, an increasing PC incidence might reflect the PC‐predisposing impact of CP. Thus, we recommend careful follow‐up for patients presenting with a recently diagnosed CP and risk factors for PC. Abstract : What's new? Although chronic pancreatitis (CP) is a risk factor for pancreatic cancer (PC), the detection and diagnosis of PC in CP patients undergoing endoscopic therapy remains a challenge. Moreover, no consensus guidelines exist for PC screening in CP patients. This retrospective analysis shows that the likelihood of diagnosing PC in CP patients is highest within two years of initial CP diagnosis. Analyses further identify biliary stricture and older age at CP onset as prognostic factors for PC development. Elevated PC incidence early in CP follow‐up may reflect previously missed PC diagnoses, whereas later PC diagnosis potentially reflects predisposing impacts of CP.